Analyzing the Potential for Utilization of New Renewable Energy to Support the Electricity System in the Cianjur Regency Region - Aryo De Wibowo Muhammad Sidik; Zafar Akbar (FIDELITY : Jurnal Teknik Elektro, 2021)
Energy is one of the basic human needs to support activities whose numbers continue to increase along with population and economic growth. On the other hand, most of the energy used today comes from fossil-based energy which has non-renewable properties so its reserves will run out if used continuously. Indonesia in general and the Cianjur region of West Java Province, in particular, has a wide variety of potential for new and renewable energy spread over most of its territory, including solar energy, wind energy, bioenergy, marine energy, and geothermal. This study aims to map the potential of New Renewable Energy in the Cianjur area to support the government's target of achieving the national energy mix and encourage energy diversification in the electricity system. The results of the study indicate that there is a large potential for renewable energy from various types of energy in the Cianjur area which can be utilized in the conversion process into electrical energy.